Hadis Ditinjau Dari Segi Kuantitas Dan Kualitasnya Serta Perspektif Kebahasaan Arab Pada Teks Hadis - Ummu Fadhilah Imran Ibrahim; Erwin Hafid; Abustani Ilyas (Jurnal Ilmu Agama Indonesia, 2026)
The examination of hadith in the present era necessitates a scholarly framework that does not solely concentrate on verifying the authenticity of the sanad and matn, but also integrates the Arabic linguistic dimension as a key factor in the formulation of textual meaning. In the midst of the widespread utilization of hadith within digital public arenas and Islamic educational institutions, the urgency to reinterpret hadith as a dynamic intellectual discourse that evolves in line with socio-religious transformations has become increasingly evident. This research is directed toward investigating hadith through three principal dimensions: the quantitative scope of transmission, the qualitative credibility of the sanad and matn, and the structural features of Arabic linguistic expression. The study adopts a qualitative paradigm with a library research design. Its data are derived from classical hadith collections and authoritative references in hadith scholarship, including Muqaddimah Ibn al-Ṣalāḥ, Nuzhat al-Naẓar, and Tadrīb al-Rāwī, complemented by contemporary academic works that discuss the advancement of hadith criticism methodology and Arabic linguistic analysis. The data were processed through descriptive-analytical and thematic procedures in order to explore the interconnection between classical hadith principles, Arabic linguistic structures, and the formation of textual interpretation. The results reveal that the quantitative aspect of hadith functions in charting transmission networks and establishing epistemic authority. Meanwhile, the qualitative dimension contributes to reinforcing the reliability of the sanad and matn within a rigorous critical framework. The Arabic linguistic dimension, on the other hand, highlights the necessity of scrutinizing structural patterns, lexical choices, and semantic elements as fundamental bases for comprehending the contextual meaning of hadith. From a theoretical perspective, this research enhances the consolidation of ʿUlūm al-Ḥadīth through the synthesis of textual and linguistic perspectives, whereas from a practical standpoint, its outcomes are anticipated to encourage the development of more context-responsive approaches to hadith learning in academic environments and contemporary Muslim communities.